Genome-wide identification of the B3 gene family in soybean and the response to melatonin under cold stress - Ren, Chunyuan; Wang, Huamei; Zhou, Zhiheng; Jia, Jingrui; Zhang, Qi; Liang, Changzhi; Li, Wanting; Zhang, Yuxian; Yu, Gaobo (Frontiers in Plant Science, 2023)
Introduction Melatonin is a multipotent molecule that exists widely in animals and plants and plays an active regulatory role in abiotic stresses. The B3 superfamily is a ubiquitous transcription factor with a B3 functional domain in plants, which can respond temporally to abiotic stresses by activating defense compounds and plant hormones. Despite the fact that the B3 genes have been studied in a variety of plants, their role in soybean is still unknown. Methods The regulation of melatonin on cold resistance of soybean and the response of B3 genes to cold stress were investigated by measuring biochemical indexes of soybean. Meanwhile, the genome-wide identification of B3 gene family was conducted in soybean, and B3 genes were analyzed based on phylogeny, motifs, gene structure, collinearity, and cis-regulatory elements analysis. Results We found that cold stress-induced oxidative stress in soybean by producing excessive reactive oxygen species. However, exogenous melatonin treatment could increase the content of endogenous melatonin and other hormones, including IAA and ABA, and enhance the antioxidative system, such as POD activity, CAT activity, and GSH/GSSG, to scavenge ROS. Furthermore, the present study first revealed that melatonin could alleviate the response of soybean to cold stress by inducing the expression of B3 genes. In addition, we first identified 145 B3 genes in soybean that were unevenly distributed on 20 chromosomes. The B3 gene family was divided into 4 subgroups based on the phylogeny tree constructed with protein sequence and a variety of plant hormones and stress response cis-elements were discovered in the promoter region of the B3 genes, indicating that the B3 genes were involved in several aspects of the soybean stress response. Transcriptome analysis and results of qRT-PCR revealed that most GmB3 genes could be induced by cold, the expression of which was also regulated by melatonin. We also found that B3 genes responded to cold stress in plants by interacting with other transcription factors. Discussion We found that melatonin regulates the response of soybean to cold stress by regulating the expression of the transcription factor B3 gene, and we identified 145 B3 genes in soybean. These findings further elucidate the potential role of the B3 gene family in soybean to resist low-temperature stress and provide valuable information for soybean functional genomics study.